Analysis of Spatial and Temporal Variation of Summer Precipitation in Xijiang River Basin and Its Causes - SUN Wen; WANG Yue; YANG Congjian; LIANG Binlan (Renmin Zhujiang)
To explore the distribution and change rule of summer precipitation in Xijiang River Basin,and provide scientific reference for agricultural production,flood control and drought relief,this paper analyzes the abrupt change,trend,space distribution and change rule of precipitation in Xijiang River Basin from 1965 to 2014 by the Mann-Kendall test,power spectrum analysis method,linear trend method,precipitation center and standard deviation ellipse method.The results show that:①From 1965 to 2014,summer precipitation in Xijiang River Basin showed a fluctuating and decreasing trend.Especially,in the 1980s,the decreasing trend reached a significant level.②The variation degree of summer precipitation in the east of Xijiang River Basin was greater than that in the west.Meanwhile,the high value center in June and August were relatively consistent,and located in the middle and east of Xijiang River Basin,contrary to that in July.③The center of summer precipitation in the Xijiang River Basin is located in Donglan,Duan,Bama,Dahua and other places in Guangxi,showing an east-west distribution.④In terms of genetic analysis,the South Asia high,ENSO and PDO anomalies had positive effects on precipitation.At the same time,altitude was positively correlated with precipitation,while temperature was negatively correlated with precipitation.